Hubungan Gangguan Pendengaran Terhadap Kualitas Hidup Pada Pasien Dewasa Di Rumah Sakit Daerah Gunung Jati Cirebon - Maulana, Rizki; Basyir, Pahmi Budiman Saputra; yusuf, Ade (Syntax Corporation, 2025)
Hearing loss is a global health problem that seriously impacts the quality of life of various age groups. WHO data shows that more than 430 million people require rehabilitation, and this number is expected to increase to 700 million by 2050. In Indonesia, the prevalence of hearing loss reaches 4.6% and can appear from childhood to adulthood. In adulthood, this condition is often undiagnosed due to its progressive nature, thus affecting mental health, social interactions, functional independence, and increasing the risk of dementia. This disorder also impacts social participation and overall quality of life. To determine the relationship between hearing loss and quality of life in adult patients at Gunung Jati Regional Hospital in Cirebon, a regional referral hospital with adequate facilities. This observational analytical study with a cross-sectional design involved 48 adult patients in the ENT-KL clinic using consecutive sampling. The research instruments were the WHOQOL-BREEF questionnaire and audiometry tests to assess hearing loss. The Spearman test showed a very significant and strong negative relationship between the level of hearing loss and quality of life (p = 0.000; r = -0.765). The higher the level of hearing loss, the lower the patient's quality of life. There is a significant relationship between the level of hearing loss and quality of life in adult patients at RSD Gunung Jati Cirebon.